Drying effect of green apple (Maluspumila) on its physicochemical properties, antioxidant activity and total phenolic content - DILIP S; M. MAHESH KUMAR; S. PERIYAR SELVAM (International Journal of Pharma and Bio Sciences, 2017)
Evidence suggests that a diet higher in fruits and vegetables may decrease the risk of Ceaseless diseases and thus the aim of this work is to compare the phytochemicals TPC and antioxidant activity of different crude extracts of freeze dried and tray dried green apple powder.(Malus pumila). In vitro phytochemical screening for all the crude extracts showed a positive result for alkaloid, flavonoid, saponin, tannin and terpenoids compounds. Thus acetone, hexane and ethanol extracts were used for further tests. The antioxidant activity of freeze dried crude extracts to DPPH was in the order of acetone> hexane > ethanol. However, the order of antioxidant activity for tray dried organic crude extracts to DPPH was in order of hexane > acetone > ethanol extract. The TPC of tray dried sample extract was found to be hexane>acetone>ethanol, similarly freeze dried sample extract was found to be acetone>hexane>ethanol. The result obtained in present study indicated Malus pumila as a rich source of natural antioxidants, and provides evidence that solvent extract of Malus pumila especially the hexane extracts contains medicinally important bioactive compounds and this justifies the use of the fruit as traditional medicine for the treatment of various diseases.